Analisis kesesuaian lahan budidaya keramba jaring apung (KJA) di teluk Parepare, Kecamatan Suppa, Kabupaten Pinrang - Ukkas Hamzah; Asbar Asbar; Rustam Rustam; Mappile Mappile; Randi Randi (Departemen Akuakultur FPIK UNDIP, 2023)
The potential resources in the coastal area of Parepare Bay are potentials that have promising economic value, especially in the fisheries sector. coastal space management planning in Parepare Bay for integrated and sustainable fisheries. The purpose of this study is an analysis of the suitability of Parepare Bay coastal land for Floating Net Karamba (KJA). The research was conducted in a qualitative method by collecting data through interviews, observations, and documentation during April to June 2021. Based on the description in the results of research and discussion that the use of coastal land in Parepare Bay for floating net cages (KJA) cultivation is still feasible and appropriate, but it needs to be regulated and arranged by involving all stakeholders so that KJA cultivators can be maximized. Keywords: Land Suitability; Floating Net Cage Cultivation; Parepare Bay.